The illustrated directory of submarines of the world - Miller, David (David M.O.) (MBI Pub. Co., 2002)
This book gives illustrations of all major classes of submarines, from man-powered submersibles to nuclear-powered missile carriers, from 1860 to the present; more than 270 submarines are described in detail, with 330 contemporary photographs and more than 50 color artworks.